The pharmacokinetics of cefepime in various health conditions: a review article - Viktaria, Venansi; Kusumasari, Dyah; Usni Putri, Saifa; Chintyasari, Shaula; Mustofa (Indonesian Journal of Pharmacology and Therapy, 2025)
Cefepime is one of fourth-generation cephalosporins which has been proven to have activity against a wide spectrum of Gram-positive and Gram-negative bacterias. It induces lysis in bacterias by disrupting the cell wall synthesis. In this review, we presented the pharmacokinetic profile cefepime in subjects with various healthconditions, such as in healthy adults, in patients with hematological malignancies, in critically ill patients, as well as in patients with renal impairment. According to various studies, such conditions could alter the pharmacokinetic profile of cefepime, especially on the excretion profile. Nevertheless, it is concluded thatcefepime could still be given all subjects, either with and without underlying conditions.